The Impact of Theology on Disaffiliation, Disengagement, and Disbelief - Raymond, Christopher D. (Journal of empirical theology, 2024)
While the reasons for the differences in the growth rates of conservative and liberal churches are well studied, one important potential reason for this difference has received little attention. The argument that liberal theology undermines the basis of belief implies that those with liberal theological views may be more likely to lose faith and disaffiliate than those holding conservative theologies that reinforce adherents’ religious faith and practice. Using a nationally representative panel survey of the American public, the analysis performed here shows that those with liberal theologies were significantly more likely to disaffiliate from Christianity, attend church less often, and cease believing in God between the two waves of the survey than those with more conservative theologies. On the basis of these findings, more attention should be given to the role that theology may play in understanding patterns of secularization.